A patient with recurrent strokes: multimodal imaging reveals two possible causes - Giusca Sorin; Schreck Johannes; Karck Matthias; Korosoglou Grigorios (Sciendo, 2022)
An underlying cardio-embolic cause can be identified in a fifth of stroke patients. Cardiac tumors occur rarely in routine clinical practice but can cause severe complications such as heart failure, valve dysfunction, embolic events, or sudden cardiac death. Herein we present the case of a 67-year-old patient with a history of recurrent stroke in whom a patent foramen ovale (PFO) and a hypermobile structure attached to the aortic valve were diagnosed during a transesophageal examination. The structure was interpreted to be a papillary fibroelastoma. Coronary computed tomography angiography completed the diagnosis, helping to exclude a relevant coronary artery disease. The patient underwent an uneventful cardiac surgery with removal of the hypermobile structure and closure of the PFO. The histopathological analysis, however, was negative for elastin in the elastin stain, and thus the diagnosis of a cardiac fibroma was made. The case emphasizes the role of cardiovascular imaging in stroke patients as well as that of histopathological analysis.